Integrasi Pendidikan Lingkungan Hidup Melalui Masyarakat Pedesaan Sebagai Alternatif Menciptakan Kawasan Hijau Dengan Memanfaatkan Sampah Botol Plastik Sebagai Media Tanam Toga Dengan Sistem Vertikultur - Kurniawan, Agung (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
The purpose of this paper is the utilization of plastic waste as a means of cultivation of toga with vertikultur system through environmental education in the community. Implementation method using stages that there is action research class. The results of research, In the first cycle of the process of securing a toga made by the community in accordance with the target. Strategic location supports the community to plant toga with vertikultur system. However, the community is still less maximal in the process of pergas daily toga. In the second cycle, the gowns are varied, the containers used in different colors, and the location is widespread. Treatment of toga has increased, people are starting to care about the toga that has been planted. In addition, the toga is also used by the community for everyday purposes